Upaya Penurunan Nyeri Pasien Spondilitis Tuberkulosis Post Debridement Stabilisasi Vertebral Servikal 4-5 - Kurnianingsih, Endang Tri; , Okti Sri Purwanti, S. Kep, Ns, M. Kep, Ns, Sp. Kep. MB (2017)
Background: Cervical tuberculous spondylitis is a disease caused by tuberculosis bacteria inflammation that occurs in the cervical spine area. Spondylitis at the cervical spine area has a 2-3% incidence of tuberculosis spondylitis cases in Indonesia. One of the problems that arise in the cervical tuberculous spondylitis are pain postoperatively. One ndling of postoperative pain is to teach pharmacologicaltechniques. Objective: provide nursing care as well as taking action in the form of relaxation breaths to decrease the patient's pain. Methods: Descriptive study approach in Intensive Care Unit (ICU) on February 21-23, 2017. The data was collected through medical records, interviews with patients and families of patients, physical examination, observation, documentation studies from journal, books, and nursing care starts from the assesment, diagnose, intervention, lementation, and evaluation as a reference to conducted by the author. Results: There was a decrease postoperative pain after the relaxation action deep breath. Conclusion: Relaxation breath proven effective in reducing the scale of postoperative pain in patients. Suggestion: The author is expected relaxation of breath can be applied as a nurse independent action to reduce the problem of pain patients in the hospital